Observation of heavy metal hazard on processed frozen escolar (Lepidocybium flavobrunneum) fillets. Issue 1 (March 2021) - Sipahutar, Y H; Sumiyanto, W; Panjaitan, P S T; Sitorus, R; Panjaitan, T F C; Khaerudin,; R
Abstract: Heavy metals are one of the most dangerous hazards of food products. This study aims to determine the processing flow of frozen escolar fish fillets by observing the cold chain process. The research methods are carried out by applying cold chain, as well as testing the quality and safety of raw material and final products. The parameters tested were Total Plate Count (TPC), histamine, heavy metal tests, and observation of the application of Hazard Analysis Critical Control Point (HACCP) at PT. XYZ, as well as descriptive data analysis and heavy metal monitoring observations. The results showed the quality of raw materials and final products organoleptic values of 8, TPC of 5.5 x10 3 and 5.5x10 2, histamine of 2.1 ppm and 2.4 ppm, and heavy metals of raw materials (lead 0.057 mg/kg, cadmium 0.011 mg/kg, mercury 0.037 mg/kg - 0.410 mg/kg). PT. XYZ establishes Critical Control Points (CCP) at the stage of receiving raw materials, metal detecting, and packing and labelling. Supervisor and testing of heavy metal mercury are carried out every three months, lead and cadmium are carried out every six months, on raw materials from each supplier enter the company. Sampling for heavy metal testing was carried out on three size groups, namely size 10-20 kg, size 20-30 kg, and size 30 kg. In conclusion, the organoleptic value, TPC, histamine and heavy metal (mercury, lead and cadmium) were in accordance with the standard. This is the result of the application of the international standard HACCP, which ensures the quality of frozen fish fillet to provide food quality and safety for consumers.